Interkoneksi Pemilihan dan Perjanjian dalam Yesaya 42:1-9 sebagai Dasar Hidup Menggereja - Gideon Hasiholan Sitorus (IAKN Ambon, 2022)
The narrative of the Servant of the LORD in Isaiah 42:1-9 is a projection that will be realized in the present and future. I define that the Servant of the LORD who experiences the election is the communal Nation of Israel. The purpose of this article is to analyze the Servant of the LORD narrative in Isaiah 42:1-9 through Gerhard von Rad's diachronic analysis, as this method penetrates into the layers of the Old Testament with the aim of revealing Israel's